2022
DOI: 10.1149/10701.7553ecst
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Soils Affected by Sewage Waste Pollution

Abstract: Soil pollution has become one of the major issues in current era. Increasing population, industrialization, and human activities have contributed immensely to increase in sewage waste. Undisposed and poorly managed sewage waste has contaminated soil and water resources badly and affected their dielectric properties. In this study, the dielectric properties of soil affected by sewage waste pollution have been presented in the broadband frequency region of 200 MHz to 14 GHz with the use of open ended coaxial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Chaudhary et al, [12] investigated the dielectric constant of urea-water solutions across a wide range of frequencies and concentration. Prachi palta et al, [13] reported the effect of sewage pollution in altering dielectric properties of soils in the broadband region. Vivek Yadav et al, [14] observed that there is a variation in the dielectric constant of mixture of water content with fertilizers.…”
Section: Dielectric Constantmentioning
confidence: 99%
“…Chaudhary et al, [12] investigated the dielectric constant of urea-water solutions across a wide range of frequencies and concentration. Prachi palta et al, [13] reported the effect of sewage pollution in altering dielectric properties of soils in the broadband region. Vivek Yadav et al, [14] observed that there is a variation in the dielectric constant of mixture of water content with fertilizers.…”
Section: Dielectric Constantmentioning
confidence: 99%
“…This is similar to the observations made by NavarKhele et al (2009), in their research findings on the effect of organic and inorganic products on the dielectric constants of soil samples. Palta et al (2022) reported slight non-linear increment in the soil dielectric constant as the organic matter (sewage) volume in the soil increases; a situation that is attributed to higher alkali concentration in organic manure, which aids electrolyte formation in the soil. The higher dielectric constant values recorded in the CS samples treated with organic materials can be linked to the higher moisture content in the AXT 2 and AXT 3 soil samples.…”
Section: Effect Of Remediation On the Soil Electrical Properties: Die...mentioning
confidence: 99%